PENGENDALIAN KUALITAS PRODUK SACHET MINUMAN SERBUK MENGGUNAKAN METODE SIX SIGMA DMAIC - Rizka Oktaviani; Heru Rachman; Muhammad Rifky Zulfikar; Muchammad Fauzi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
This study aims to identify problems related to quality and provide suggestions for improvement using the Lean Six Sigma approach. This Six Sigma approach will be used in the analysis of the powder drink production process at PT. ABC with DMAIC method (Define, Measure, Analyze, Improve, Control). The define stage aims to determine the aims and objectives of the research. The measure stage measures production performance with the current number of defects where the company currently has a DPMO performance of 3844.4 with a sigma value of 4.165. The analyze stage identifies the root problem that causes defects in the product using the fishbone diagram method. The improve stage takes corrective action based on the root of the problem identified in the fishbone diagram. The control stage is a follow-up after an improvement has been made to the system. Based on the results of the implementation of the DMAIC Six Sigma method, there are potential benefits that can be obtained by the company. To increase the sigma value, several improvement steps are proposed, including: Implementing predictive maintenance, training and coaching operators, using spare parts that are in accordance with machine specifications, providing feedback to suppliers regarding the poor quality of packaging materials